Hi there! Thank you for the opportunity to help you with your question!
We need to complete the square in order to write g(x) in vertex form:
g(x) = -2( x^2 - 2 x + 2)
= -2( (x-1)^2 +1)
= -2(x-1)^2 -2
And the vertex is at the point (h,k) in this case, (1,-2)
g(x) = -2( x^2 - 2 x + 2) so this is the quadratic function in form
g(x) = -2(x-1)^2 -2 is the equation in vertex form
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?